PENANAMAN NASIONALISME PELAJAR MILENIAL TANPA NARKOBA MELALUI PEMENTASAN MONOLOG - Kristiono, Natal; Astuti, Indri (Harmony, 2018)
Nationalism needs to be planted to the next generation of this milestone of struggle which will then be continued by the next generation. Drug abuse becomes a problem that cannot be overcome. Many cases illustrate the more terrible problem. Many cases illustrate the horrific problems. To solve the problem of drug abuse cannot only be solved by one party. In accordance with the formulation of the problem and the purpose of the study, the focus of the research was the cultivation of millennial nationalism without drugs applied in the TexmacoPemalang Vocational School which included personal and procedural procedures. Current millennial students with good technological mastery can access information quickly but with negative impacts that also need to be watched out.There have been many patterns of drug abuse prevention.The pattern of drug prevention continues to be developed as a form of our concern in overcoming the threat of this country. Students have the opportunity to explore information, process and convey to others as their role in education.   Nasionalismeperluditanamkanke generasi berikutnya dari tonggak perjuangan ini yang kemudian akan dilanjutkan oleh generasi berikutnya. Penyalahgunaan narkoba menjadi masalah yang tidak bisa diatasi. Banyak kasus mengilustrasikan masalah yang lebih buruk. Banyak kasus mengilustrasikan masalah yang mengerikan. Untuk memecahkan masalah penyalahgunaan narkoba tidak bisa diselesaikan oleh satu pihak. Sesuai dengan rumusan masalah dan tujuan penelitian, fokus penelitian adalah penanaman nasionalisme milenium tanpa obat yang diterapkan di Sekolah Kejuruan Texmaco Pemalang yang termasuk prosedur pribadi dan prosedural. Siswa milenium saat ini dengan penguasaan teknologi yang baik dapat mengakses informasi dengan cepat tetapi dengan dampak negatif yang juga perlu diawasi. Ada banyak pola pencegahan penyalahgunaan narkoba. Pola pencegahan narkoba terus dikembangkan sebagai bentuk kepedulian kami dalam mengatasi ancaman negara ini. Siswa memiliki kesempatan untuk mengeksplorasi informasi, proses dan menyampaikan kepada orang lain sebagai peran mereka dalam pendidikan.